Quality effects of operative delay on mortality in hip fracture treatment. Issue 5 (29th September 2005) - Sund, R; Liski, A
Abstract : Background: Most hip fracture patients undergo surgery, but there is conflicting evidence on the relation between the timing of surgery and the outcome of treatment. There is considerable variation in the length of surgical delays between hospitals, possibly reflecting the quality of care. Aim: To examine the associations between in-hospital surgical delay and the mortality of hip fracture patients from a practical quality assessment perspective. Methods: The effects of operative delay on mortality were estimated using various statistical methods applied to observational data from 16 881 first time hip fracture patients aged 65 or older from 47 hospitals (providers) in Finland in 1998–2001. Results: A prolonged in-hospital operative delay was associated with a higher mortality of hip fracture patients in individual level analyses, but the instrumental variable approach indicated that the individual level effect was not caused by the operative delay but by inappropriate methodological assumptions. There was extensive variation between providers in the proportion of late surgery patients. Provider level analyses showed that the effects of the provider of operative delay on mortality are quite small, but there is a clear association between the proportion of late surgery patients and non-optimal treatment. Conclusions: If provider level heterogeneity is not explicitly taken into account, studies of the effects of surgical delay on outcomes are prone to serious bias. The proportion of patients with prolonged waiting time for surgery at the provider level seems to work as an effective evidence-based quality indicator. Providers should reduce unnecessary delays to surgery and identify more carefully patients not suitable for early surgery.